ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VII SMP NEGERI 16 KUPANG - Ridno Lopi; St Muthmainnah Yusuf; Uke Ralmugiz (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
The purpose of this study is to analyze the mathematical representation capabilities of junior high school students. This research has been conducted at SMP Negeri 16 Kupang School Year 2019/2020. The method used in the study was a descriptive analysis method, which involved 76 students as samples. The student's mathematical representation ability test instrument used as many as 3 questions in the form of descriptions. The results revealed that students' mathematical representation skills in Comparative materials had an average score of 72.51. Students' mathematical representation ability on symbol representation indicators with an average of 85.33 is higher than the verbal representation and image representation indicators; image representation indicator with a score of 60 is still below average; and verbal representation indicators have an average of 72.66. There are several factors that affect the level of ability of mathematical representation of students, including students still find it difficult to convert mathematics symbols into images, turn math problems into mathematical symbols or models and convey mathematical ideas using their own language and words. The ability of students to solve math problems using symbol and verbal representation is quite satisfactory while students use image representation is not maximal.